2021
DOI: 10.1021/acs.est.0c06927
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Isotope Fractionation during Adsorption and Substitution with Iron (Oxyhydr)oxides

Abstract: Cadmium (Cd) isotopes have great potential for understanding Cd geochemical cycling in soil and aquatic systems. Iron (oxyhydr)­oxides can sequester Cd via adsorption and isomorphous substitution, but how these interactions affect Cd isotope fractionation remains unknown. Here, we show that adsorption preferentially enriches lighter Cd isotopes on iron (oxyhydr)­oxide surfaces through equilibrium fractionation, with a similar fractionation magnitude (Δ114/110Cdsolid‑solution) for goethite (Goe) (−0.51 ± 0.04‰)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 77 publications
6
61
0
Order By: Relevance
“…13 Researchers have identified the main Cd sources and their contribution to Cd pollution by determining the Cd isotope ratios of various sources and contaminated receptors (e.g., soil and sediments). [14][15][16][17] Cd isotope fractionation also occurs during its adsorption-desorption between the solid and liquid phases [18][19][20] and translocation to different plant tissues (e.g., roots, shoots, and grains). 21,22 These observations have demonstrated that Cd isotope analysis is a promising tool for tracing the sources of Cd in contaminated sites and can also be used as an indicator for probing the behavior of Cd in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…13 Researchers have identified the main Cd sources and their contribution to Cd pollution by determining the Cd isotope ratios of various sources and contaminated receptors (e.g., soil and sediments). [14][15][16][17] Cd isotope fractionation also occurs during its adsorption-desorption between the solid and liquid phases [18][19][20] and translocation to different plant tissues (e.g., roots, shoots, and grains). 21,22 These observations have demonstrated that Cd isotope analysis is a promising tool for tracing the sources of Cd in contaminated sites and can also be used as an indicator for probing the behavior of Cd in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Goethite nucleation and growth occur mainly through the dissolution-recrystallization, while that for hematite primarily via a solid-state transformation through internal dehydrationrearrangement. 57,59,60 The existence of a relatively high concentration of remaining AlIJIII) anions in solution of the HNP systems may favor the transformation of the primary ferrihydrite particles immediately formed after OH − addition to hematite rather than goethite, through adsorption onto ferrihydrite to inhibit the mineral dissolution but promote the ferrihydrite aggregation and further structure rearrangement, similar to the effect of phosphate on the ferrihydrite transformation. 61 And this effect decreases in the order HNPs > HNCs > HNRs.…”
Section: Implications For the Effects Of Al On Hematite Morphology An...mentioning
confidence: 99%
“…in soils and natural waters have been mostly reported (Zhuang et al, 2021). Manganese oxides are the strongest natural mineral oxidants in the environments (Peacock and Moon, 2012;Yan et al, 2021). Many studies on soils and sediments have found very high correlations between Tl and Mn in the reducible mineral fraction (Cruz-Herna ́ndez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%